Effectiveness of rotavirus vaccination against childhood diarrhoea in El Salvador: case-control study. (15th June 2010) - de Palma, Orbelina; Cruz, Lilian; Ramos, Hector; de Baires, Amada; Villatoro, Nora; Pastor, Desiree; de Oliveira, Lucia Helena; Kerin, Tara; Bowen, Michael; Gentsch, Jon; Esposito, Douglas H; Parashar, Umesh; et al.
Abstract : Objective To evaluate the effectiveness of a monovalent rotavirus vaccine against severe rotavirus disease and to assess its impact on diarrhoea in children aged less than 2 years after national introduction in El Salvador, a low-middle income country in Central America. Design Matched case-control study. Setting Seven hospitals in cities across El Salvador, January 2007 to June 2009. Participants 323 children aged less than 2 years admitted with laboratory confirmed rotavirus diarrhoea and 969 healthy controls matched for age and neighbourhood. Main outcome measure Effectiveness of rotavirus vaccination ((1–adjusted odds ratio of vaccination)×100) against rotavirus diarrhoea requiring hospital admission. Results Cases and controls were similar for breast feeding, premature birth, maternal education, and socioeconomic variables. G1P[8] strains were identified in 92% of rotavirus cases. Effectiveness of two doses of vaccination against diarrhoea requiring hospital admission was 76% (95% confidence interval 64% to 84%). Protection was significantly lower (P=0.046) among children aged 12 months or more (59%, 27% to 77%) compared with children aged 6-11 months (83%, 68% to 91%). One dose of vaccine was 51% (26% to 67%) effective. At the sentinel hospitals, all admissions for diarrhoea among children under 5 declined by 40% in 2008 and by 51% in 2009 from the prevaccine year 2006. Conclusions A monovalent rotavirus vaccine was highly effective against admissions for rotavirus diarrhoea in children aged less than 2 years in El Salvador and substantially reduced the number of such admissions in this low-middle income setting. The impact on disease epidemiology after vaccination, particularly among older children, warrants future attention.